Enhancing Critical Thinking Skills in Biology Subject with the Legendary Model of Cooperative Learning - Ibrahim Ibrahim; Marwan Marwan; Juli Firmansyah (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine students' critical thinking skills by implementing jigsaw cooperative learning compared to conventional learning in the concept of environmental pollution in Aceh Senior High School, Indonesia. The method used was an experimental method with a pre-test-posttest control design. It used two classes, class X-1 as the experimental class with 20 students and X-2 as the control class with 20 students. The instrument used was a test of Critical Thinking Skills on the concept of environmental pollution. The data of student test results were processed using the independent sample t-test with SPSS version 18.0 at a significant level of 0.05. The analysis results show differences in students thinking abilities, indicated by tcount > ttable, which is 6.633> 2.68 for students critical thinking. There were differences in students' critical-thinking skills between those using the jigsaw cooperative model and students using conventional learning in learning the concept of environmental pollution at the senior high school in Aceh Province, Indonesia.